Correction: Özdel et al. Modeling of the Potential Distribution Areas Suitable for Olive (Olea europaea L.) in Türkiye from a Climate Change Perspective. Agriculture 2024, 14, 1629 - Muhammed Mustafa Özdel; Beyza Ustaoğlu; İsa Cürebal (Agriculture)
In the original publication [...]